Are U.S. Organizational Concepts And Measures Transferable To Another Culture? An Empirical Investigation - Sekaran, Uma (Academy of Management Journal, 1981)
The article presents information on a study which illustrated a multivariate cross-cultural approach to explore the meaning of job involvement (JI) and job satisfaction (JS) in the United States and India. The author gathered information from over 250 white collar workers in U.S. and Indian banks. Twenty predictors used in this study were organized into four categories, demographic characteristics, personality characteristics, job characteristics, and organizational climate factors. The survey found that factor analysis is equally applicable to both cultures. The survey also found that an employee's attitude toward the importance of his or her own job is an important predictor of JI. In terms of JS, job variety and job stress were found to be the predictors common to both cultures.